2003
DOI: 10.1097/00000542-200304000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Adenosine Triphosphate–regulated Potassium Channel Opening Acts as a Trigger for Isoflurane-induced Preconditioning by Generating Reactive Oxygen Species

Abstract: The results indicate that mitochondrial K(ATP) channel opening acts as a trigger for isoflurane-induced preconditioning by generating ROS in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 23 publications
4
56
1
Order By: Relevance
“…Isoflurane-induced preconditioning was prevented by 5-hydroxydeanoate and gadolinium, suggesting the involvement of mechanogated channels in this phenomenon (Piriou et al, 2000). Administration of K ATP channel blocker before isoflurane administration completely blocked the cardioprotection (Tanaka et al, 2003). Isoflurane preconditioning may act via release of small quantities of free radicals to protect myocardium against infarction in rabbits (Mullenheim et al, 2002;Tanaka et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…Isoflurane-induced preconditioning was prevented by 5-hydroxydeanoate and gadolinium, suggesting the involvement of mechanogated channels in this phenomenon (Piriou et al, 2000). Administration of K ATP channel blocker before isoflurane administration completely blocked the cardioprotection (Tanaka et al, 2003). Isoflurane preconditioning may act via release of small quantities of free radicals to protect myocardium against infarction in rabbits (Mullenheim et al, 2002;Tanaka et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…It is suggested that mitochondrial K ϩ channels, often identified as effectors of protection by preconditioning, could be these mediators (10,27,32,34). However, their role in this mechanism is questionable since their activation has been correlated with both increase and decrease in ROS production (20,49). These controversial findings may result from differential behavior of these channels depending on the metabolic state of the cell (44).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption was supported by findings that activation of K ATP channel plays important roles both in the cardiac and cerebral preconditioning. [21][22][23][24] The possible involvement of adenosine A 1 receptors as mediators of cardiac preconditioning has been proven by studies in several animal models. 7,25,26 It has been suggested that adenosine receptors may be activated by preconditioning and, in turn, activate K ATP channels, possibly through an intermediate such as PKC.…”
Section: Discussionmentioning
confidence: 99%